The Implementation of Traditional Games in Supporting the Holistic Development of Early Childhood in Islamic Educational Institutions - Sitepu, Hestika Dewi (Al-Fikru: Jurnal Ilmiah, 2025)
This research examines the application of traditional games in supporting holistic early childhood development at Al Azhar Medan Model Kindergarten. Early childhood development is essential to shape physical, cognitive, social and emotional aspects. With the rapid development of digital technology, traditional games are often forgotten, even though they have proven benefits in child development. This research aims to explore how games such as jump rope, gobak sodor and congklak can improve motor, cognitive and social skills in early childhood. Using a qualitative approach and phenomenological method, data was obtained through interviews with teachers, parents, and children, as well as classroom observations. The results showed that traditional games have a positive impact on children's motor coordination, cognitive ability and social interaction. However, challenges such as limited time in the curriculum, lack of parental understanding, and limited resources were also found. This study suggests that traditional games should be further integrated in early childhood education to support more holistic development.